Polymorphisms in the HTR2A and HTR3A Genes Contribute to Pain in TMD Myalgia - Louca Jounger, Sofia; Christidis, Nikolaos; Hedenberg-Magnusson, Britt; List, Thomas; Svensson, Peter; Schalling, Martin; Ernberg, Malin (Frontiers in Oral Health, 2021)
Background: The aim of this study was to investigate if single nucleotide polymorphisms (SNPs) related to monoaminergic neurotransmission, in particular the serotonergic pathway, contribute to pain perception in patients with temporomandibular disorder (TMD) myalgia and if there is a correlation to jaw function as well as psychosocial factors such as stress, anxiety and depression. Materials and Methods: One hundred and nineteen individuals with TMD myalgia were included. A venous blood or saliva sample was taken for genetic analyses and genotyped regarding HTR2A (rs9316233) HTR3A (rs1062613), HTR3B (rs1176744), SERT (5-HTTLPR; rs25531) and COMT (Val158Met; rs4680). A clinical examination according to Diagnostic Criteria for TMD (DC/TMD) was performed and axis I and II data were compared between participants with different genotypes for each gene using Kruskall-Wallis test. The characteristic pain intensity (CPI) was tested for correlations to scores for the Perceived Stress Scale, Generalized Anxiety Disorder, and Patient Health Questionnaires using Spearman’s rank correlation test with Bonferroni correction for multiple testing. To further explore data factor analysis was performed to identify latent factors associated to the outcome variables. Results: The results showed that the CPI was higher in participants with the HTR3A C/T genotype compared with the gene variants (P = 0.032). Similarly, for HTR2A there was a trend towards higher CPI values in participants with the C/G genotype (P = 0.051). Furthermore, there were positive correlations in several SNPs in each gene between CPI and psychosocial distress but no clear pattern between certain combinations of SNPs and other variables was detected. The factor analysis identified two latent variables. One was positively correlated to the HTR3B gene, jaw function and self-reported parafunctions, and the other was positively correlated to psychological distress and negatively correlated to SERT. Conclusion: Taken together, the polymorphism rs1062613 in the HTR3A gene contributes to higher pain in TMD myalgia. This together with positive correlations between pain variables and psychological factors strengthens that pain and psychological distress share similar mechanisms and that polymorphisms in genes related to the serotonergic and catecholamine systems are involved.